2016
DOI: 10.1111/scd.12157
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mouth breathing in children with ­developmental ­disabilities

Abstract: Among patients with -developmental disabilities, boys and psychotropic drug users had a greater chance of being mouth breathers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
1
17
0
4
Order By: Relevance
“…Children with cerebral palsy are at risk of developing significant respiratory problems due to insufficient respiratory muscle strength . In this sample, where epilepsy is common, mouth breathing is associated with the consumption of anticonvulsant medication . The medication used for its control (especially benzodiazepines) is capable of producing respiratory depression, hypoventilation, hypoxia, and obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with cerebral palsy are at risk of developing significant respiratory problems due to insufficient respiratory muscle strength . In this sample, where epilepsy is common, mouth breathing is associated with the consumption of anticonvulsant medication . The medication used for its control (especially benzodiazepines) is capable of producing respiratory depression, hypoventilation, hypoxia, and obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…13 In this sample, where epilepsy is common, mouth breathing is associated with the consumption of anticonvulsant medication. 14 The medication used for its control (especially benzodiazepines) is capable of producing respiratory depression, hypoventilation, hypoxia, and obstructive sleep apnea. The mechanisms involved in this process are related to the elimination by the action of the anticonvulsant from the chemical and neural control of respiration or by decreasing the wakefulness by altering the duration of sleep stages or decreasing the amount of REM (rapid eyes movements) stage.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, an inverse relationship exists in this context, and people who have greater health needs are the ones who receive the least amount of care (2). This is also evident when it comes to the oral health of marginalized groups, like those with mental, intellectual or behavioral challenges, and physical disabilities (3)(4)(5). It is observed that similar to other marginalized groups, people with learning disabilities also have poorer oral hygiene status and a higher prevalence of dental caries and periodontal disease (6,7).…”
Section: Introductionmentioning
confidence: 86%
“…The literature describes the prevalence of mouth breathing as ranging from 5% to 75% of children tested [20][21][22][23]. It is probable that the oral cavity is dry because the mouth M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%